(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
In this paper an application for evaluation and control of software projects is presented. The novelty of this application is that it has been developed using an extended database management system with fuzzy logic. In addition to the usual tasks of a project control tool, this application allows to evaluate the management of a project, taking into consideration the benefits of fuzzy queries.